A Review on Diagnosis and Management of Conjunctivitis - Mahima R. Patil; Mansi B. Patil; Hitendra S. Chaudhari; Sunil P. Pawar; Rahul B. Lovhare; Roshan M. Chaudhari (Recent Trends in Infectious Diseases, 2024)
Conjunctivitis, typically recounted as crimson eye, is a super ocular circumstance affecting men and ladies of all ages. This abstract aims to summarize the findings of a comprehensive study that delves into the pathogenesis, clinical manifestations, and management strategies for conjunctivitis. A multifaceted approach was employed, including a systematic literature review of conjunctivitis-related studies, clinical observations, and interviews with leading ophthalmologists. The various cases were analysed to assess demographic patterns, etiological factors, and treatment outcomes. Our study reveals that conjunctivitis presents with a spectrum of etiologies, including viral, bacterial, allergic, and environmental triggers. The pathogenesis of conjunctivitis involves complex interactions between infectious agents, host immune responses, and environmental factors. Viral conjunctivitis is highly contagious and typically self-limiting, whereas bacterial conjunctivitis often necessitates antibiotic therapy. Allergic conjunctivitis, delivered on via capability of allergens such as pollen or dust, responds applicable to antihistamines and environmental modifications. Additionally, the study highlights emerging trends in conjunctivitis management, including the use of novel antiviral agents and the potential for targeted immunotherapy.
Keywords: Pathogenesis; allergic conjunctivitis; bacterial conjunctivitis; conjunctivitis; management; ophthalmology; pink eye; viral conjunctivitis